2021
DOI: 10.3389/fpsyg.2021.696813
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Model of Self-Regulation and Healthy Habits as an Individual Protective Tool in the Context of Epidemics–Evidence From COVID-19

Abstract: Objective: The present study aims to explore the mediation role of self-regulation on health-related behaviors adoption or maintenance, mental health, and well-being during the COVID-19 confinement in a sample of adults in Portugal.Design: One-hundred fifty individuals (118 females, 32 males; Mage = 33.57 year; SD = 12.71) filled an online survey to assess self-regulation, healthy behaviors, mental health, and well-being perception, during the early months of the pandemic (June–August, 2020).Main Outcome Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
1
13
1
Order By: Relevance
“…The studies involved a total of 13,631 university students from Brazil, Colombia, Spain, Portugal, Chile, Poland, and Mexico. All studies used the FANTASTIC questionnaire; however, some studies evaluated all the dimensions of the questionnaire [ 5 , 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], while others only evaluated some dimensions, such as nutrition, consumption of alcohol, tobacco or drugs, physical activity, and sleep.…”
Section: Resultsmentioning
confidence: 99%
“…The studies involved a total of 13,631 university students from Brazil, Colombia, Spain, Portugal, Chile, Poland, and Mexico. All studies used the FANTASTIC questionnaire; however, some studies evaluated all the dimensions of the questionnaire [ 5 , 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], while others only evaluated some dimensions, such as nutrition, consumption of alcohol, tobacco or drugs, physical activity, and sleep.…”
Section: Resultsmentioning
confidence: 99%
“…They used spiritual and religion dimensions, mindful, transcendence meditation. Selfregulation seems to be a good indicator of adopting a healthy lifestyle and better mental health and wellbeing in the context of the COVID-19 pandemic [30]. Previous study found that COVID-19 distress and general mental distress were strongly related both meaningfulness and self-control were negatively associated with general mental distress [31].…”
Section: Discussionmentioning
confidence: 96%
“…The score ranges of psychological distress; mild level (≤ 51), moderate level (52-81), and severe level (≥82). Then, the score ranges of coping; mild level (≤ 28), moderate level (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and high level (≥46).…”
Section: Instrumentsmentioning
confidence: 99%
“…Our results showed that few coping strategies were identified by the participants; however, those who reported using physical exercise or breathing activities as coping strategies had lower anxiety scores. People who maintained healthy behaviors, such as healthy eating, exercise, impulse control, and the ability to manage adverse events, showed positive results for the maintenance of mental health and well-being during a study carried out in Portugal (Sousa et al, 2021 ). This suggests that providing education on coping strategies can be useful in helping people manage and prevent anxiety in stressful and traumatic situations, such as those experienced during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%